Atomically sharp crack tips in monolayer MoS2 and their enhanced toughness by vacancy defects. - Wang, S; Qin, Z; Jung, G; Martin-Martinez, F; Zhang, K; Buehler, M; Warner, J (American Chemical Society, 2016)
When a brittle material fractures due to an applied stress, cracks propagate through the material causing mechanical failure. Atomically sharp crack tips at the frontier of crack propagation are predicted but have not been captured experimentally before, which requires both, atomic resolution and crack tracking at much larger length scales. Here, we combine both in-situ aberration-corrected transmission electron microscopy and large-scale molecular dynamics simulations based on a reactive force field to investigate the crack propagation in the monolayer MoS2 with atomic resolution. We find that brittle fracture in 2D monolayer MoS2 leads to crack tips with atomic sharpness through the preferential Mo-S bond cleavage along the zigzag lattice direction with least energy release. We show that vacancy defects cause crack deflections, while increasing defect density shifts the fracture mechanism from brittle to ductile by the migration of vacancies in the strain fields and forming a defect network. We demonstrate that adding vacancies to MoS2 can enhance the fracture toughness of the material by forming defect lines, rendering its crack propagation different from, and leading to even higher fracture toughness, than defected graphene. We show that this mechanism explains the reduced crack propagation speed by adding vacancies as seen in experiments.